Diagnosing the local suitability of high-rise timber construction. Issue 1 (2nd January 2020) - Goubran, Sherif; Masson, Tristan; Walker, Thomas
ABSTRACT: High-rise timber construction has attracted increasing attention among academics and practitioners in recent years. Publications place a heavy emphasis on the ecological and economic benefits of timber construction, but they pay less attention to the applicability of the technique to the local context. This paper proposes ten parameters that are used to develop a diagnostic tool to assess the suitability of a given location for the construction of high-rise timber buildings. The parameters cover economic, social, environmental, technical, and policy issues. Through visual representation of the outputs, the tool can be used to compare the merits of timber construction in different locations. Three locations are used to demonstrate the applicability of the diagnostic tool: the province of British Columbia (Canada), the state of São Paulo (Brazil), and the province of Quebec (Canada). An analysis of these locations reveals the capacity of the tool to identify the barriers, risks, and development opportunities for each location. Integrated design teams, developers, policymakers, and institutions could use this tool when selecting or proposing the structural material for building projects. Future development of the tool should aim to incorporate quantitative measures.